Real Time Validation of EKF Estimator for Low Speed Estimation in DTC IMD - Mini R; Binoj P.V.; B. Hariram Satheesh; Dinesh M.N. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Low speed estimation in DTC IMD is not accurate due to the presence of transient offset, drift and domination of ohmic voltage drop in the measured stator voltages and currents used for estimating the stator flux required for accurate estimation of speed. EKF is a nonlinear, recursive adaptive algorithm capable of estimating speed ranging from very low speed to rated speed using equation of motion from noisy measured currents and voltages based on state space technique. In the previous work a new state space model of IM was developed for estimation in EKF by feeding load torque profile as an input variable instead of estimating it by considering load torque as constant, validated using MATLAB-Simulink software. In this paper real time validation of the EKF controller with load profile fed as input for speed estimation in DTC IMD is carried out using OPAL-RT simulator and real time results validates the simulation results and proves the effectives of the new EKF for low speed estimation in DTC IMD